(untitled)
We analyse life-cycle saving decisions when households use simple heuristics, or rules of thumb, rather than solve the underlying intertemporal optimization problem. We simulate life-cycle saving decisions using three simple rules and compute utility losses relative to the solution of the optimization problem. Our simulations suggest that utility losses induced by following simple decision rules are relatively low. Moreover, the two main saving motives re ected by the canonical life-cycle model long-run consumption smoothing and short-run insurance against income shocks can be addressed quite well by saving rules that do not require computationally demanding tasks such as backward induction., address = München, author = Joachim K. Winter and Kathrin Schlafmann and Ralf Rodepeter, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, doi = 10.5282/ubm/epub.12334, keywords = D91; E21; 330; saving; life-cycle models; bounded rationality; rules of thumb; Sparen; Lebenszyklus; Konsumtheorie; Zeitpräferenz; Beschränkte Rationalität; Einkommenshypothese; Entscheidung bei Unsicherheit; Theorie, language = eng, note = urn:nbn:de:bvb:19-epub-12334-9, number = 2011-16, publisher = Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, title = Rules of Thumb in Life-Cycle Saving Decisions, type = Munich Discussion Paper, url = https://hdl.handle.net/10419/104347, year = 2011